Aproximación al aprendizaje de las habilidades implicadas en la expresión oral en los estudiantes de 10mo año de Educación General Básica en la Unidad Educativa “Pío Jaramillo Alvarado” de la ciudad de Loja - Silva Silva, Byron Mauricio (2023)
The objective of this research work is to analyze the learning process of the skills involved in oral expression, through knowledge of the importance of social interaction and the determination of barriers that hinder its development. A qualitative research approach was used, with a research design with a descriptive scope. The non-participant observation technique was applied, through a registration form; the semi-structured interview was also used. As participants, we have Basic General Education students. In the results it is determined that the majority of the students do not have or do not comply with these skills, demonstrating a deficient development in oral expression. Keywords: skills, oral expression, technique, learning, students.